Recent advances on microplastics/nanoplastics interaction with plant species: A concise review / Nurfarwizah Adzuan Hafiz, Nurin Nabilah Jalaudin Basha, Mohamed Syazwan Osman - Adzuan Hafiz, Nurfarwizah; Jalaudin Basha, Nurin Nabilah; Osman, Mohamed Syazwan (Universiti Teknologi MARA Shah Alam, 2023)
The transmission, toxicity, and removal of micro/nanoplastics (MPs/NPs) have been the subject of extensive attention and have impacted concerns globally. The inclusion of microplastic pollution can have a plethora of effects on plant growth, depending on the composition of the planting media. Following a recent year of research focusing mostly on aquatic systems, attention has begun shifted to the consequences of microplastic on plant cells. Therefore, there is a significant knowledge gap regarding the extent to which MPs have an impact on terrestrial environments, particularly agroecosystems, and the risks that this has for human health. Within this review, the interaction of MPs/NPs to plant species is due to the abundance of microplastics in soil following human activity. This review also summarised the routes of MPs/NPs to the plant through the root and shoot of the plant. Subsequently, the emergence of MPs/NPs influences and brings implications on plant growth, growth, and crop production according to each plant species. Besides, the recommendations for further research on the phytotoxic effects of MPs on plants, the method of uptake and translocation in plant tissues, detection techniques for MPs in plants, and, most importantly, the potential for future interactions and accumulation of MPs in plants have also been discussed thoroughly in this paper. The most recent developments in this area are summarised at the end, with an emphasis on the future directions for studying microplastics in terrestrial systems.